Dens agenesis and cervical vertebral malformation in a Labrador Retriever puppy - Salas EN (Dove Medical Press, 2014)
Elisa N Salas,1 Henry E Cerny,2 Seth P Harris1 1Institute of Agriculture and Natural Resources, School of Veterinary Medicine and Biomedical Sciences, University of Nebraska–Lincoln, Lincoln, NE, USA; 2Yankee Hill Veterinary Hospital, Lincoln, NE, USA Abstract: Cervical vertebral malformations can cause acute or progressive pain, paralysis, and potentially death. Herein we present a case report of dens agenesis; cervical vertebral malformations of C1, C2, C6, and C7; subluxation of C1 and C2 and C4 and C5; and associated degenerative myelopathy in a 5-month-old female Labrador Retriever puppy. We additionally review current knowledge regarding pathogenesis and treatment. Keywords: atlantoaxial subluxation, cervical vertebral malformation, dog, dens agenesis, myelopathy